CUTANEOUS REACTIVITY OF IMMUNE AND HYPERSENSITIVE RABBITS TO INTRADERMAL INJECTIONS OF HOMOLOGOUS INDIFFERENT STREPTOCOCCUS AND ITS FRACTIONS - McEwen, Currier (The Rockefeller University Press, 1935)
Rabbits were immunized intravenously with intact indifferent streptococci, with homologous P fraction, and with an emulsion of mechanically ground cocci; others were sensitized by intravenous injection of the intact microorganisms. Their serologic and dermal reactions to these materials and to the homologous S fraction were compared with those of normal animals. The dissociation, in certain instances, between circulating antibody and dermal reactivity was noteworthy. From the results the following conclusions were drawn. 1. Intradermal injection of a soluble streptococcal protein into a rabbit immunized intravenously with that protein leads to the immediate anaphylactic type of skin response; while similar dermal testing of a rabbit sensitized by intracutaneous inoculation of the intact microorganism induces the delayed (tuberculin) type of response. 2. The induction of the immediate type of dermal reaction to streptococcal protein requires more than the mere presence of a high serum precipitin titer to that protein. 3. Lesions of the immediate type can be induced by the intradermal injection of a streptococcal carbohydrate into rabbits immunized intravenously with intact cocci and showing a high serum precipitin titer to that carbohydrate. 4. Intravenous immunization of rabbits with an emulsion of mechanically ground indifferent streptococci leads to the production of only non-type-specific antibodies. 5. It is possible that carbohydrate as well as protein fractions of indifferent streptococci are capable of eliciting the delayed type of dermal response in rabbits intracutaneously sensitized with that microorganism.